Is wealth found vertically or horizontally? - Singh, Gurpreet (2015)
This paper examines the impact of horizontal and vertical takeovers on U.S acquirers over the short and long run. A sample of large transactions over ten years is investigated to answer whether acquirers benefit more from horizontal or vertical merger. The method used to identify horizontal and vertical merger used by this investigation is the SIC code and the BEA input-output accounts. The investigation suggests little evidence that horizontal and vertical mergers have significantly different impacts on the returns of the acquirers.